Strategi Peningkatan Aspek Keuangan dan Manajerial Koperasi Seruni Putih - Zulfatun Ruscitasari; Nailul Fithroh; Rifqi Syarif Nasrulloh (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
This research aims to: (1) analyze monetary and managerial condition at Seruni Putih Cooperative now, (2) determine and recommend the right strategy to improve monetary and managerial aspect of Seruni Putih Cooperative. Research method used in this research is qualitative descriptive. Data retrieval techniques are carried out with interviews, observations and documentation. Data analysis techniques are using SWOT analysis. By analyzing the strengths, weaknesses, opportunities and threats, it will further facilitate to compose the right strategy in improving the financial and managerial aspects of Seruni Putih Cooperative. The results of this study show that to improve the financial aspects in Seruni Putih Cooperative can use the following strategies: (1) improve the quality of performance, both in carrying out RAT and lending services in cooperatives, (2) make letters of agreement when borrowing to minimize bad credit, (3) regenerate cooperative managers so that productivity in cooperatives is more optimal. Strategies that can be applied to improve managerial aspects in Seruni Putih Cooperative are: (1) utilizing the knowledge gained from the training of the Department and other institutions to improve the quality of Human Resources in cooperatives, (2) maximize opportunities for local resources to increase cooperative capital, (3) optimize their own capital by increasing compulsory savings.